A Three-Phase Multicriteria Method to the Supplier Selection Problem - Mendoza, Abraham; Santiago, E; Ravindran, A Ravi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
This paper describes a new multi-criteria method to solve the general supplier selection problem. The supplier selection problem is complicated and risky, owing to a variety of qualitative and quantitative factors affecting the decision-making process. For this matter, we present a unique three-phase methodology to reduce the base of potential suppliers to a manageable number and optimize the allocation of orders by means of multi-criteria techniques, namely ideal solution approach, Analytical Hierarchy Process (AHP) and Goal Programming (GP). Finally, a real-life example is provided to illustrate how the method can be used in practice.